Knowledge management practices (KMP) and academic performance in Universiti Teknologi Mara (UiTM) Terengganu, Malaysia - Muhammad, Norrini; Ab Rahman, Baharom; Wan Abdul Rahman, Wan Zuhaila; Idris, Asma' Rashidah; Md Sabri, Sabiroh; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Knowledge management is one of the significant fields in the current organization in order to improve the performance. The aim of this study was to investigate the relationship between knowledge management practices and academic performance in public institution of higher learning. A questionnaire was used as the main instrument for the data collection. A total of 100 respondents answered the questionnaires which represented 54% of response rate. It was found that knowledge management practices namely knowledge generation, knowledge codification, knowledge sharing and knowledge utilization had positive and significant relationship with academic performance. Thus, in order to achieve higher academic performance, UiTM Terengganu has to ensure that the knowledge management practices were excellent.